3D displays - Lueder, Ernst 1932-; Society for Information Display (Chichester John Wiley & Sons, 2012)
This book addresses electrical engineers, physicists, designers of flat panel displays (FDPs), students and also scientists from other disciplines interested in understanding the various 3D technologies. A timely guide is provided to the present status of development in 3D display technologies, ready to be commercialized as well as to future technologies. Having presented the physiology of 3D perception, the book progresses to a detailed discussion of the five 3D technologies: stereoscopic and autostereoscopic displays; integral imaging; holography and volumetric displays, and:Introduces spati.
Cover; Wiley-SID Series in Display Technology; Title Page; Copyright; Dedication; Preface; Series Preface; Introduction; Chapter 1: The Physiology of 3D Perception; 1.1 Binocular Viewing or Human Stereopsis; 1.2 The Mismatch of Accommodation and Disparity and the Depths of Focus and of Field; 1.3 Distance Scaling of Disparity; 1.4 Interocular Crosstalk; 1.5 Psychological Effects for Depth Perception; 1.6 High-Level Cognitive Factor; Acknowledgments; Optical Society of America (OSA); References; Chapter 2: Stereoscopic Displays; 2.1 Stereoscopic Displays with Area Multiplexing.
Prof. Sandra Mae W. Famador (Recommending faculty) : BS Computer Science Program
Includes bibliographical references and index.
Keywords: Three-dimensional display systems